Insurance Sector In India A Journey Since It’S Inception: A Historical Perspective and Future Outlook (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Insurance sector in India is one of the booming sectors of the economy and is growing at the rate of 15-20 percent per annum. Together with banking services, it contributes to about 7 percent to the country's GDP. Insurance sector in India was liberalized in March 2000 with the passage of the Insurance Regulatory and Development Authority (IRDA) Bill. This lifted entry restrictions for private players and allowed foreign players to enter the market with some limits on direct foreign ownership. There is a 26 percent equity cap for foreign partners in an insurance company and a proposal to increase this limit to 49 percent. The opening up of the insurance sector has led to rapid growth of the sector. The potential for growth of insurance industry in India is immense as nearly 80 per cent of Indian population is without life insurance cover while health insurance and non-life insurance continues to be well below international standards. The insurance sector in India has come up with a full circle from being an open competitive market to nationalization and back to a liberalized market again. Tracing the developments in the Indian insurance sector reveals the 360 degree turn witnessed over a period of almost two centuries. The US$ 41 billion Indian life insurance industry is considered the fifth largest life insurance market, and growing at a rapid pace of 32-34 percent annually.